The We Propose Project! Little Great Citizens - Claudino, Sérgio (Aprender, 2025)
The tradition of Geography in schools is divided between the study of the world and the study of the country. Since the local scale is undervalued, it has been advocated since the 17th century for the first years of schooling. Having its origins in secondary education, the Nós Propomos!/We Propose Project, to which the name Little Great Citizens is added in elementary school, challenges children to identify local problems and present proposals for their resolution. The project can be developed by groups of students or, mostly, is carried out within the group-class context, where the teacher has a greater role. The Nós Propomos! has been developed in several countries and has had good results. More than the projects developed by students, some of which have already been completed, we are witnessing an important development of citizenship education.